The role of silica and alkaline earth metals with biomolecules in the biomineralization processes: the eggshell's formation and the crystallization in vivo for x-ray crystallography. Issue 1 (February 2020) - Elejalde-Cadena, Nerith Rocío; Cuéllar-Cruz, Mayra; Moreno, Abel
Abstract: This contribution is a scientific journey divided into three parts. In the first part, we review the role that silica biomorphs of alkaline earth metals have played in the formation of complex structures as a reminiscence of the chemistry of the primitive life on Earth. These biomorphs, and their variety of forms synthesized by simple chemical reactions, can nowadays be experimentally used to explain some mechanisms of biomineralization in living organisms. In the second part, we review the role of calcium carbonates in the formation of eggshells in avian. The mechanism of the mineral eggshell´s formation of the biogenic calcite deposited on an organic matrix is revised. The competitive crystal growth mechanism of the mineralized part orientates these crystals preserving the semispherical shape of the egg. We are using these eggshell formations as a second model to understand the biomineralization processes in Nature. The third and final part is about the importance that biomineralization concepts have to produce hybrid materials for the future. This has allowed us to obtain tailored size control of complex morphologies by synthetic chemical procedures that give rise to these new materials' specific forms and ad hoc properties. We conclude this part with the advantage of knowing the biological mechanisms, based on molecular biology concepts, to obtain protein crystals in vivo and in cellulo techniques. Both methods use the cellular machinery of growing biocrystals in specialized cells that have evolved through millions of years. This new way of producing protein crystals has been trending topic for modern crystallography when using the facilities of the X-ray free-electron lasers (four generation of synchrotrons) for megahertz serial crystallography.